Technical efficiency estimates of paddy farming in peninsular Malaysia : a comparative analysis - Ismail, Mohd Mansor; Idris, Nurjihan; Hassanpour, Behrooz (Scholars Research Library, 2013)
Estimating technical efficiency of production techn ology is important for policy purposes, particularl y for a sector which has strategic importance in self sufficiency level such as paddy farming. This study compared te chnical efficiency of paddy farming in east coast and west coast of Peninsular Malaysia by using data envelopm ent analysis (DEA) and Stochastic Frontier Analysis (SFA). Prima ry data were collected using a set of structured qu estionnaire from 230 farmers in east coast and west coast of Pe ninsular Malaysia. The data are analyzed by using D EA and SFA. The results indicated that the differences in methodologies employed produced different efficienc y estimates. The DEA result showed that efficiency score for Pen insular Malaysia is 56%, which is lower from the ef ficiency score obtained using the SFA at 69%. Due to the lar ge differences in technical efficiency results, rec ommendation for policy purpose should not depend on only one me thod as it is inaccurate.